Analisis Pengaruh Peran Masyarakat dalam Pembangunan Pendidikan Agama Islam di Indonesia: Analysis of the Influence of Community Roles in the Development of Islamic Religious Education in Indonesia - Siti Umi Kulsum; Dzihab Aminudin S; M. Zulfikar Sulkhi Aunillah (Al-Ma‘ani: Journal of Islamic Studies, 2026)
Islamic education plays an important role in forming individuals who are religious and have noble character. However, to achieve this goal, Islamic education cannot stand alone. The role and position of the community have a significant impact on shaping the direction and quality of this religious education system. This research aims to analyze the influence of the community's role in the development of Islamic religious education in Indonesia. The method used is library research with a descriptive qualitative approach, where data is collected from various literatures such as books and relevant scientific journals using content analysis techniques. The results show that the community has an obligation to maintain the continuity of education as a shared responsibility between the government, family, and educational institutions. There are three main factors that necessitate good communication between educational institutions and the community: changes in the nature of teaching, community expectations regarding educational changes, and the development of democratic thinking. Furthermore, community involvement can be carried out individually or organizationally, ranging from the use of services to decision-making in the development of madrasah.